Reproductive Characteristics of Female Egg-carrying Buntingi, Xenopoecilus oophorus, an Endemic Fish to Lake Poso in Central Sulawesi - Gundo, Meria Tirsa; Rahardjo, Muhammad Fadjar; Batu, Djamar Tumpal Frederik Lumban; Hadie, Wartono (UI Scholars Hub, 2016)
Reproduction characteristic of female egg-carrying buntingi, Xenopoecilus oophorus had been studied. This research was conducted at Lake Poso, Central Sulawesi, Indonesia. Specimens were collected monthly from August 2012 to July 2013 at four sampling stations around the lake. Macroscopic observations of ovarian maturity level and gonadosomatic index revealed a long reproductive period during the rainy season, with four spawning peaks in November, January, February and April. The highest total fecundity was 135 oocytes, and the highest batch fecundity was 36 oocytes. Analysis of the oocyte diameter frequency distribution showed X. oophorus is a multiple spawner. Batch fecundity was correlated (r = 0.78) with body weight.